MENTAL HEALTH INTEGRATION IN GERI PACT. (11th November 2018) - Kube, E; Hicken, B; Moye, J; Harris, G; Sullivan, J
Abstract: Integration of mental health care into primary care is one important strategy to engage older adults in behavioral health care who otherwise can have mental health conditions which go under-diagnosed and treated. We present the results of two studies that examine mental health care within GeriPACT. In a national survey of GeriPACT providers (N=101), 28.7% report having a psychiatrist team member (M=.20 FTE), and 29.7% report having a psychologist team member (M=.24 FTE), usually as an "extended" not "core" team member, most commonly focusing on psychosocial issues (82.2%), depression (79.2%), and dementia (79.2%). In a second focused survey of psychologists in GeriPACT's a range of referral practices are described, with 80% providing same day access with clinical activities including brief cognitive assessment, psychotherapy (most often cognitive-behavioral), and caregiver support. Qualitative analyses will further illustrate the range of obstacles and rewards in integrated MH care in GeriPACT.